Search for a Higgs boson decaying into a b-quark pair and produced in association with b quarks in proton–proton collisions at 7 TeV - Chatrchyan, S.; Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Aguilo, E.; Bergauer, T.; Dragicevic, M.; Erö, J.; Fabjan, C.; Friedl, M.; Frühwirth, R.; et al. (Elsevier BV, 2013)
A search for a neutral Higgs boson decaying to a pair of b quarks, and produced in association with at least one additional b quark, is presented. Multijet final states with three jets identified as originating from b quarks, at least one of which may include a non-isolated muon, are studied. The data used in this analysis correspond to an integrated luminosity of 2.7-4.8 inverse femtobarns, collected by the CMS experiment in proton-proton collisions at the LHC at a center-of-mass energy of 7 TeV. This search is particularly sensitive to Higgs bosons in scenarios of the Minimal Supersymmetric Model (MSSM) with large values of tan(beta). No excess over the predicted background from standard model processes is observed. Stringent upper limits on cross section times branching fraction are derived and interpreted as bounds in the MSSM tan(beta) and M[A] parameter-space. Observed 95% confidence level upper limits reach as low as tan(beta) approximately 18 for M[A] approximately 100 GeV.

Replaced with published version. Added journal reference and DOI
Keywords: Benchmark scenarios; [PHYS.HEXP] Physics [physics]/High Energy Physics - Experiment [hep-ex]; CMS; Higgs; MSSM; Physics; Nuclear and High Energy Physics; cms; Standard model; Level; FOS: Physical sciences; Benchmark scenarios; Standard model; MSSM; LHC; Particle; Masses; Level; CMS; Physics; Higgs; MSSM; Particle physics; Large hadron collider; CMS; High Energy Physics - Experiment; High Energy Physics - Experiment (hep-ex); cms; higgs; mssm; physics; [PHYS.HEXP]Physics [physics]/High Energy Physics - Experiment [hep-ex]; Physic; Masses; info:eu-repo/classification/ddc/530; Fisica delle particelle; CMS; Physics; ddc:530; Large hadron collider; CMS; Higgs; MSSM; Physics; QC Physics / fizika; Physique des particules élémentaires; Particle physics; LHC; Particle; LHC; CMS; Higgs boson; B quark; physics; Higg; Higgs; MSSM